2019
DOI: 10.1111/evo.13733
|View full text |Cite
|
Sign up to set email alerts
|

Population structure promotes the evolution of costly sex in artificial gene networks

Abstract: We build on previous observations that Hill–Robertson interference generates an advantage of sex that, in structured populations, can be large enough to explain the evolutionary maintenance of costly sex. We employed a gene network model that explicitly incorporates interactions between genes. Mutations in the gene networks have variable effects that depend on the genetic background in which they appear. Consequently, our simulations include two costs of sex—recombination and migration loads—that were missing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 71 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…That these early studies of inbreeding and heterosis are relevant to the evolution of sex and recombination is not a new idea [11,20,21], and is subsumed under Lewontin's general proclamation that "every discovery in classical and population genetics has depended on some sort of inbreeding experiment" [20,22,23]. Since these early studies, several more recent studies have shown that different kinds of population structure can create conditions that make recombination across locally-evolving subpopulations favorable [10][11][12][24][25][26][27][28][29]. These studies find that population structure can help to maintain the variation without which recombination would be neither advantageous nor disadvantageous, and they identify conditions under which recombination is advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…That these early studies of inbreeding and heterosis are relevant to the evolution of sex and recombination is not a new idea [11,20,21], and is subsumed under Lewontin's general proclamation that "every discovery in classical and population genetics has depended on some sort of inbreeding experiment" [20,22,23]. Since these early studies, several more recent studies have shown that different kinds of population structure can create conditions that make recombination across locally-evolving subpopulations favorable [10][11][12][24][25][26][27][28][29]. These studies find that population structure can help to maintain the variation without which recombination would be neither advantageous nor disadvantageous, and they identify conditions under which recombination is advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…Components X (n) and Y (n) , therefore, while not What we have shown so far is that, if recombination occurs across the products of natural selection, such as fixed genotypes in different populations, subpopulations, demes or competing clones, the resulting offspring should be more fit than their parents, on average. This effect provides novel insight into established observations that population structure can favor recombination [29][30][31][32][33] and may even speak to notions that out-crossing can create hybrid vigour (heterosis).…”
Section: Settingmentioning
confidence: 79%
“…; Whitlock et al. ) and cooperation (Nowak ; Taylor and Nowak ) in sufficiently structured populations. Similar to its effect on mutators, population subdivision allows costly recombiner alleles to persist in a metapopulation despite indirect selection against the recombination load—the cost of unfavorable combinations of alleles.…”
Section: Resultsmentioning
confidence: 99%